2007
DOI: 10.1016/j.cell.2007.03.015
|View full text |Cite
|
Sign up to set email alerts
|

α2A-Adrenoceptors Strengthen Working Memory Networks by Inhibiting cAMP-HCN Channel Signaling in Prefrontal Cortex

Abstract: Spatial working memory (WM; i.e., "scratchpad" memory) is constantly updated to guide behavior based on representational knowledge of spatial position. It is maintained by spatially tuned, recurrent excitation within networks of prefrontal cortical (PFC) neurons, evident during delay periods in WM tasks. Stimulation of postsynaptic alpha2A adrenoceptors (alpha2A-ARs) is critical for WM. We report that alpha2A-AR stimulation strengthens WM through inhibition of cAMP, closing Hyperpolarization-activated Cyclic N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
753
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 607 publications
(802 citation statements)
references
References 43 publications
29
753
0
2
Order By: Relevance
“…Indeed, stimulation of a 2A -ARs does not always enhance working memory function. For example, iontophoresis of a low dose of guanfacine (at 5 nA) enhances delay-related firing, while a high dose (at 50 nA) does not (see Figure 2b of Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, stimulation of a 2A -ARs does not always enhance working memory function. For example, iontophoresis of a low dose of guanfacine (at 5 nA) enhances delay-related firing, while a high dose (at 50 nA) does not (see Figure 2b of Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies show that stimulation of a 2 -ARs enhances PFC neuronal activity that is related to working memory Wang et al, 2007), while blockade of a 2 -ARs inhibits the working memory-related PFC neuronal activity Sawaguchi and Yamane, 1999;Wang et al, 2007). However, it is poorly understood how a 2 -ARs regulate synaptic transmission in the PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Given the beneficial effects of clonidine and related a 2 agonists on prefrontal cortical function (Li et al, 1999;Wang et al, 2007) as well as the important role of the prefrontal cortex in the positive actions of a 2 agonists on spatial working memory (Arnsten and Goldman-Rakic, 1985;see Arnsten, 2004 for review), it is likely that if clonidine improves memory in either model, this phenomenon would be linked to enhanced prefrontal cortical function. In the case of animals with hippocampal damage, the enhancement of prefrontal function could act to compensate for the loss of hippocampal modulation of spatial working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Our work showed that both systemic administration and local infusion of guanfacine into the PFC improve visuomotor associative learning [70,75] . Using an iontophoretic technique, stimulation of α 2A -adrenoceptors in the PFC was found to increase the spiking activity associated with working memory in behaving monkeys [37,76] .Neuronal activity in the PFC associated with working memory can be enhanced by α 2A -adrenoceptor stimulation through cAMP-HCN signaling pathways [76,77] . Our work suggested that under normal physiological conditions, the α 2A -adrenoceptors in pyramidal cells can be activated through Gi-cAMP-HCN signaling [78] .…”
mentioning
confidence: 99%
“…On the other hand, PFC functions might occur via the Gi-cAMP-PKA-CaMKII-AMPAR signaling pathway [76] . Both mechanisms together optimize the synaptic inputs to pyramidal neurons and determine the synaptic outputs for PFC cognitive functions.Indeed, it has been reported that guanfacine at relatively high doses suppresses evoked excitatory postsynaptic currents, and has no enhanced effect or even suppresses delay-related activity [76] . conform to a theoretical rationale for ADHD, account for the neurobiology, and respond to therapeutic interventions both behaviorally and pharmacologically [79] .…”
mentioning
confidence: 99%